Disordered random matrices. (March 2015) - Pato, M P
Abstract: A revision is made of the effect, in the statistical properties of the matrices of random matrix theory, of dividing them by a positive random variable. As the method preserves unitary invariance analitical derivations are easily performed. It is shown that the same procedure applied to the adjacency matrices of random graphs gives rise to a family of graphs that interpolates between the Erdos-Renyiand the scale-free model. Previous applications and new ones are discussed.